General index of Shupihui: Revista Latinoamericana de Actualidad y Análisis (1976-1990) - Carranza Orbegoso, Jorge (2021)
The index records the content of 52 issues of Shupihui: Revista Latinoamericana de Actualidad y Análisis from the year of its creation in 1976 to its last edition in 1990. The general index presents chronologically the contents of each issue in ascending order from the first to the last issue. The articles maintain the consecutive order and the corresponding pagination.